Аналіз алгоритму та специфіка створення концептуального дизайну персонажів - Коваленко, О. О. (ХНУРЕ, 2024)
This study delves into the intricacies of character design concepts. It examines the fundamental principles behind creating characters and explores various techniques used in crafting compelling character designs.
Keywords: концептуальний дизайн персонажів; візуальне мистецтво